Etude des groupements d'adventices dans le Maroc occidental - Douira, A.; Taleb, A.; El Antri, M.; Fadli, M.; Salhi, S.; Zidane, L. (Biotechnologie, Agronomie, Société et Environnement, 2010)
Study of the weeds groupings in western Morocco. An ecological floristic study was carried out in the principal areas of Morocco severely infested by the sterile oats. From 110 readings taken in cereals, the 324 listed species belong to 47 botanical families including 39 dicotyledons. Six families: Asteraceae, Fabaceae, Poaceae, Brassicaceae, Caryophyllaceae and Apiaceae add up 59% of the total staff complement alone. The biological aspect shows a prevalence of the therophytes with 80%, followed by the hemicryptophytes and the geophytes with respectively 11 and 7%. Mediterranean taxa are dominating with 62% of the total staff complement. The taking into account of the index partial of noxiousness made it possible to release 27 problematic species whose Avena sterilis, Phalaris paradoxa, Phalaris brachystachys, Scolymus maculates, Lolium multiflorum, Papaver rhoeas and Lolium rigidum are most harmful by far. The factorial analysis of correspondences (A.F.C.), by the means of the edaphic variables, made it possible to highlight six ecological groups.